On variability of tranverse muscle of chest in man - Jelisiejew, Tamara (Anthropological Review, 1974)
The research work was carried out on 1056 transverse muscles of chest in man in various stages of life from foetuses to old people of both sexes. The following details were analysed: the number of indentations in the muscle, the relation of the muscle fibres to the tendon ones, the location of top and bottom borders, the course of indentations and the asymmetry of the muscle. It has been found that the transverse muscle of the chest shows a distinct tendency to reduction and that manifests itself in a decrease in the number of indentations of the muscle, in the lowering the top border as well as in that the tendon fibres serve as a substitute for the muscular ones. A considerable distinct asymmetry of the muscle is also characteristic. The muscles of the left side are on the whole larger and have a greater number of indentations than those of the right side.